PROBOLINGGO MUSEUM AS EDUCATION TOURISM 2011-2019 - Eko Muhammad Arif Budiono; Sugiyanto Sugiyanto; Bambang Soepeno; Rully Putri Nirmala Puji (History Education, University of Jember, 2021)
Probolinggo Museum is a museum in the Probolinggo City area. the Probolinggo museum has a function for the community, but the function of the museum has not been maximally utilized by the community in the field of education. The museum functions as tourism and education because museums contain elements of knowledge. The research objective was to determine the function of the Probolinggo Museum as a tourist and educational place, a source of knowledge and inspiration for the formation of the character values ​​of the museum for visitors. This research is about history, used the historical method with steps (1) Heruristic, (2) Criticism, (3) Interpretation, and (4) Historiography. The research results of the Probolinggo Museum have collections which are divided into several, including the Archaeological Collection, Ethnographic Collection, Heritage Collection, Historical Collection, Numismatic Collection, Philological Collection, Keramological Collection and Technological Collection which are the main attraction of the museum as a tourist destination. Probolinggo Museum has a source of knowledge about the history, art and culture of Probolinggo, knowledge is focused on the local area. The character values ​​of the Probolinggo Museum include religion, tolerance, love for the country, mutual cooperation and national spirit, these sources can be used as a visitor's educational character.